2019
DOI: 10.1016/j.sjbs.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sheep farming business in Uşak city of Turkey: Economic structure, problems and solutions

Abstract: The current study was conducted to reveal the current states, structural features and primary problems of the sheep raising businesses in the city of Uşak. The study group of the current study is comprised of 429 sheep raising businesses selected through stratified sampling (provinces) and a questionnaire consisted of 112 items was administered to these businesses. Through the items in the questionnaire, data were collected about the general features of the businesses and their owners, the state of grazing lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The low herd health contribution to production costs is a reality in the LAPOC/UFPR sheep production environment, which has satisfactory standards and herd health control. Health protection programmes are sometimes understood as extra costs related to sheep production; however, an increase in lamb deaths can lead to higher losses (Demirhan, 2019). In a study carried out on representative commercial farms with respect to meat lamb production, Raineri et al (2015b) noted the use of anthelmintics as one of the factors that least impacted the production costs of sheep farming, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The low herd health contribution to production costs is a reality in the LAPOC/UFPR sheep production environment, which has satisfactory standards and herd health control. Health protection programmes are sometimes understood as extra costs related to sheep production; however, an increase in lamb deaths can lead to higher losses (Demirhan, 2019). In a study carried out on representative commercial farms with respect to meat lamb production, Raineri et al (2015b) noted the use of anthelmintics as one of the factors that least impacted the production costs of sheep farming, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Raineri et al (2015a), upon analysing the elasticity of meat sheep production costs in a feedlot in Brazil, reported higher contribution margins (63%) and an elastic, positive feed increase. In Turkey's provinces, Demirhan (2019), through a questionnaire, found that the main problems identified by sheep producers were the cost of feed. Thus, the adequate management of feed costs seems to be relevant for sheep production.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous empirical findings, variable costs accounted for almost two-thirds of total expenses and fixed costs accounted for about 50% of capital expenses [25,26]. Another feature of the sector is the low prices paid for milk and meat [27]. Goat farming is labour intensive, as it requires high labour input [28].…”
Section: Introductionmentioning
confidence: 99%
“…Ovine are prevalent in numerous fluoride-affected regions worldwide, sparking increased attention to fluoride because of their growing economic importance [3]. For example, in India and Turkey, which have rich and diverse ovine germplasm resources, fluorosis continues to be a major obstacle for the ovine industry [31,32].…”
Section: Introductionmentioning
confidence: 99%